ONTOLOGICAL VIEWS OF FAZL IBN AHMAD (Scientific journal of the Fergana State University, 2025)
This article provides information on the analysis of the philosophy of existence in the work of Fazl ibn Ahmad Iddatul uqul wa umdatul abdul (The Promise of Reasons and the Basis of Things That Are Agreeable to Reasons). Existence is a philosophical category that represents the world and all kinds of existence. Philosophers have put forward various ideas about existence. In Sufism, this concept is explained as the theory of unity of existence, unity of witnessing, and unity of being. The work of Iddatul uqul wa umdatul abdul (The Promise of Reasons and the Basis of Things That Are Agreeable to Reasons) presents ideas about man and the philosophy of existence. In the construction of a new Uzbekistan, the teachings of Rumi, especially the ideas of Fazl ibn Ahmad, in today's difficult times, raising young people as spiritually mature people and spiritually elevating them remains an important task.